Crypto-Foods : Blockchain-based Decentralized Food Ordering Service - Dr. Madhur Jain,; Tanish Chugh,; Shivani Jaiswal,; Shivangi Singh,; Sahil Gupta, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The proliferation of blockchain technology has spurred innovative applications across various industries, including the food delivery sector. This paper introduces Crypto Foods, a blockchain-based food delivery application designed to enhance transparency, security, and efficiency in food delivery processes. Leveraging blockchain’s immutable ledger and smart contract capabilities, Crypto Foods ensures the integrity of transactions and provides users with unprecedented visibility into the food supply chain. This research outlines the architecture and functionalities of Crypto Foods, highlighting its potential to address key challenges such as food safety, traceability, and trust in traditional delivery systems. Furthermore, the paper discusses the technical implementation of Crypto Foods, emphasizing its decentralized nature and resistance to data tampering. Through a comparative analysis with conventional food delivery platforms, we demonstrate the advantages of Crypto Foods in fostering trust among consumers and stakeholders. Finally, we explore future directions for research and development in blockchain-based food delivery systems, underscoring the significance of Crypto Foods as a pioneering solution in this domain.
Keywords: Crypto Foods; Food Delivery Sector; Blockchain